2014
DOI: 10.4103/2277-9175.142043
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of telephonic follow up in prevention of suicidal reattempt in patients with suicide attempt history

Abstract: Background:prevention of suicide is one of priority world health. Suicide is one of the preventable causes of death. The aim of this study is evaluation of telephone follow up on suicide reattempt.Materials and Methods:This randomized controlled clinical trial is a prospective study which has been done in Noor Hospital of Isfahan-Iran, at 2010. 139 patients who have suicide attempt history divided in one of two groups, randomly, 70 patients in” treatment as usual (TAU)” and 69 patients in “brief interventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 17 publications
0
55
0
Order By: Relevance
“…Likewise, in the authors’ and colleagues’ previous study,[22] there was no significant difference in the reduction of suicide reattempts between “phone call communication,” compared with the “treatment as usual” group during 6 months follow-up, but the “phone call” group patients showed an increased hope and decreased suicidal thoughts compared with the “treatment as usual” group patients. In this study, we evaluated the “phone call” versus “face to face” follow-up, but in previous study there was not face-to-face communication, and the control group was allowed to treat as they choose.…”
Section: Discussionmentioning
confidence: 73%
“…Likewise, in the authors’ and colleagues’ previous study,[22] there was no significant difference in the reduction of suicide reattempts between “phone call communication,” compared with the “treatment as usual” group during 6 months follow-up, but the “phone call” group patients showed an increased hope and decreased suicidal thoughts compared with the “treatment as usual” group patients. In this study, we evaluated the “phone call” versus “face to face” follow-up, but in previous study there was not face-to-face communication, and the control group was allowed to treat as they choose.…”
Section: Discussionmentioning
confidence: 73%
“…Attempted suicide is the strongest exclusive predisposing factor for death due to suicide (Mousavi et al., ). Previous studies showed that 3% of those who attempt suicide die within 1 year after their attempt, 9% die within the following 5 years, and 10% die after a longer period (Cederke, Monti, & Ojehagen, ; Kapur et al., ; Nock et al., ; Nordentoft et al., ; Suominen, Isometsa, & Lonnqvist, ).…”
Section: Discussionmentioning
confidence: 99%
“…Suicide is the top‐ranked cause of death among 20‐ to 39‐year‐olds and the second‐ranked cause among 40‐ to 49‐year‐olds (Cabinet Office, ). The rate of attempted suicide is 4–10 times that of committing suicide (Mousavi, Zohreh, Maracy, Ebrahimi, & Sharbafchi, ). In many countries, suicide attempt is one of the main reasons for emergency hospitalization of young people, putting a heavy burden on health care systems (Fleischmann et al., ; WHO, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Moussavi and coll. Found no significant difference in reduction of SA recurrence between an intervention group receiving a phone call and a control group; there was a decrease of suicidal thoughts, however, in the intervention group [17].…”
Section: Introductionmentioning
confidence: 74%